EVALUATING THE CLINICAL OUTCOME OF MODIFIED MINIMALLY INVASIVE NON-SURGICAL THERAPY VS TRADITIONAL NON-SURGICAL PERIODONTAL THERAPY– A SPLIT MOUTH RANDOMIZED CONTROLLED CLINICAL STUDY - MADHUMITHA, DR. U.R.K.; RUDHRA, DR. K.; VARSHINI M, RIDHU (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
BACKGROUND: Nonsurgical periodontal therapy (NSPT), a gold standard therapy for periodontitis has undergone miraculous evolution. One of such improvisations is Modified Minimally invasive nonsurgical therapy (M-MINST). Also, these minimally invasive techniques combined with patient blood derivatives like platelet concentrates to enhance the regeneration. AIM AND OBJECTIVE: The present split mouth trial aims to compare and evaluate Modified Minimally Invasive Non-surgical Therapy (M-MINST) and Traditional Non-surgical Periodontal Therapy (T-NSPT) MATERIAL AND METHODS: The study sample included 20 patients with 40 periodontal pocket sites. The samples were divided into two groups; Group I or the test site included 20 sites which were treated with Modified Minimally Invasive Non-surgical Therapy (M-MINST) combined with I-PRF and Group II or control group included 20 sites treated with Traditional Non-surgical Periodontal Therapy (T-NSPT) along with I-PRF. Clinical outcomes; Probing Pocket Depth, Clinical Attachment Level, Bleeding On Probing were assessed at baseline, and first month. Patient related outcomes; Verbal Rating Scale (VRS), Wound Healing Index were assessed at 1st week, 2nd week and first month. RESULTS: Bleeding on Probing, Wound healing index scores, Verbal rating scale scores were comparatively lesser in the test group than the control group. A statistically significant difference was noted in Probing depth, clinical attachment level at both groups at different time periods. CONCLUSION: Both groups are found to be equally effective. M-MINST along with I-PRF was found to yield better results than T-NSPT, especially in terms of bleeding on probing, wound healing and verbal rating scale.